Pathogenesis mechanisms of endometrial polyps in women of reproductive age: a literature review - Mekan R. Orazov; Liudmila M. Mikhaleva; Olga F. Poymanova; Irina A. Mullina (Гинекология, 2022)
Endometrial polyp (EP) is a frequent incidental finding during hysteroscopy in asymptomatic patients. To date, the pathogenesis of EPs has not been fully disclosed, which challenges the primary and secondary prevention of EPs and their targeted therapy. It determined the focus of our work. We searched for scientific publications in Cochrane Library, ScienceDirect, PubMed (MEDLINE), eLIBRARY using the keywords "polyps", "endometrial polyps", "pathogenesis", "reproductive age", "recidive" for 20122022. Analysis of the literature data allowed us to conclude that ES pathogenesis most likely involves several mechanisms, both estrogen-mediated (hyperestrogenism, including related to impaired progesterone reception and deficiency) and non-hormonal (inflammatory, immune, genetic factors, neoangiogenesis). Hormonal and non-hormonal factors disturb normal cyclic changes of the endometrium during the menstrual cycle, alter the balance and dynamics of proliferation and apoptosis, and initiate neoangiogenesis that serves as a resolving mechanism of polyposis formation, persistence of ES, and their recurrence after surgical removal. The objective of our study was to analyze and summarize the scientific data available on the mechanisms of ES pathogenesis in women of reproductive age.